The Effect of Digital Teaching Modules, School Facilities, and Parental Support on the Learning Independence of Tenth-Grade Students at MAN 2 Kediri City - Nur Fadhilah Putri Utami; Bayu Surindra; Tjetjep Yusuf Afandi (Darul Yasin Al Sys, 2026)
Self-regulated learning is an essential competency that supports students’ academic success in the digital era. However, students’ learning independence is influenced by external factors, including the use of digital teaching modules, the availability of school facilities, and parental support. This study aims to examine the influence of digital teaching modules, school facilities, and parental support on the self-regulated learning of Grade X students at MAN 2 Kota Kediri, both partially and simultaneously. A quantitative approach with an explanatory research design was employed. The population consisted of 504 Grade X students, and 223 respondents were selected using random sampling based on the Slovin formula. Data were collected through questionnaires that met validity and reliability requirements and were analyzed using multiple linear regression with IBM SPSS Statistics 23. The findings indicate that digital teaching modules have a positive and significant effect on self-regulated learning, with a regression coefficient of 0.565 and a significance value of 0.000. School facilities also have a positive and significant effect, with a regression coefficient of 0.563, while parental support has a positive and significant effect, with a regression coefficient of 0.262. Simultaneously, the three independent variables significantly influence self-regulated learning, as indicated by an F-value of 157.444 and a significance value of 0.000. The coefficient of determination (R²) of 0.683 indicates that 68.3% of the variance in students’ self-regulated learning can be explained by digital teaching modules, school facilities, and parental support. This study concludes that strengthening students’ self-regulated learning requires integrated support through the optimization of digital learning technologies, adequate school facilities, and active parental involvement. The findings contribute to the literature on technology-supported learning independence and provide practical implications for schools and families in developing effective strategies to foster students’ self-regulated learning.